Servant Leadership and Creativity: A Study of the Sequential Mediating Roles of Psychological Safety and Employee Well-Being - Wang, Wenxian; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Psychology, 2022)
With today’s increasingly dynamic and competitive business environment, creativity is critical for enterprises to enhance their competitiveness. Companies today invest and seek new ways to enhance creativity of employees within the organization. Our study describes the effects of servant leadership, psychological safety, and employee well-being on creativity under the conservation of resources theory. We used a sample of 252 full-time employees in the United Kingdom who had been recruited online and collected their data for analysis. We conducted confirmatory factor analyses to test the validity of the measurement model and regression to evaluate the direct effects. Subsequently, we used bootstrapping to confirm mediation and serial mediation effects. The results showed that servant leadership was positively related to creativity and that psychological safety and employee well-being were serial mediators between them.